2020
DOI: 10.5433/1679-0359.2020v41n3p971
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, aerobic stability, and fermentation pattern of white oat silage wilted with glyphosate

Abstract: White oat has good nutritional quality but is not an easy forage to ensile due to its high buffer capacity and moisture content at ensiling moment. Therefore, wilting is necessary to offset such negative aspects. However, this process demands skilled workforce and adequate machinery. In this way, chemical desiccation is a promising technology to reduce the steps needed for wilting. Thus, we aimed to evaluate the effects of glyphosate as a chemical desiccant on the nutritional quality, fermentation pattern, los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…However, when the pH was higher than 4.2, amino acids were decomposed into ammonia, hydrogen sulfide, and amines owing to the activity of spoilage bacteria, which decreased protein quality (McDonald et al, 1991). The pH value (3.6) reported by Ribeiro et al (2014) was lower than the data (3.8–5.4) of present study; therefore, the silages in this study had more proteolysis.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…However, when the pH was higher than 4.2, amino acids were decomposed into ammonia, hydrogen sulfide, and amines owing to the activity of spoilage bacteria, which decreased protein quality (McDonald et al, 1991). The pH value (3.6) reported by Ribeiro et al (2014) was lower than the data (3.8–5.4) of present study; therefore, the silages in this study had more proteolysis.…”
Section: Discussioncontrasting
confidence: 86%
“…After grasses were ensiled, the FB and FC contents decreased, while FA content increased and became the main fraction (65–79%) of crude protein in silage, agreed with the findings of Oliveira et al (2012). However, Ribeiro et al (2014) reported that FA in napier grass silages only accounted for about 50% CP, and Andrade et al (2010) reported FB (57% CP) was the main fraction and nearly twice as abundant as FA (32% CP). The reason for these different results might be the differences in silage fermentation, because the proteolytic process was closely related to the level of the silage pH.…”
Section: Discussionmentioning
confidence: 99%